IDENTIFICATION OF NEW ICONIC OBJECTS FOR THE SUSTAINABLE DEVELOPMENT OF HERGLA (TUNISIA) - Chaggar, Meriem; Boubaker, Mohsen (International Journal of Engineering Technologies and Management Research, 2018)
This paper discusses the issue of territorial identity by facing globalization in Hergla’s delegation. In order to requalify the “image of the city”, amulticriteria analysis of the landscape units ofthe “El Medfoun” forest and the Sebkha “Halk El Menjel” has been developed to detect symbol indices of change for a new “territorial landscaping”. These natural areas were identified as new iconic objects. Indeed, the Sebkha and the forest, carrying ecological, patrimonial, social and economic values, may be integrated into a territorial project, through of landscape geomediation practices. These values are considered as identity factors for the sustainable development of Hergla delegation.